Fetal alcohol spectrum disorder among pre-adopted and foster children - Ariel Tenenbaum; Asaf Mandel; Talia Dor; Alon Sapir; Orly Sapir-Bodnaro; Pnina Hertz; Isaiah D. Wexler (BMC, 2020)
Abstract Background Fetal alcohol spectrum disorder (FASD) is a leading cause of neurodevelopmental disorders. Children in foster care or domestically adopted are at greater risk for FASD. The aim of this study was to determine the prevalence or risk for FASD in a selected population of foster and adopted children. Methods Children between 2 and 12 years who were candidates for adoption in foster care were evaluated for clinical manifestations and historical features of fetal alcohol spectrum disorder based on established criteria for FASD. Results Of the 89 children evaluated, 18 had mothers with a confirmed history of alcohol consumption during pregnancy. Two children had fetal alcohol syndrome and one had partial fetal alcohol syndrome. In addition, five had alcohol-related neurodevelopmental disorder, one had alcohol-related birth defects, and a single child had manifestations of both. Of the 71 children in which fetal alcohol exposure could not be confirmed, many had manifestations that would have established a diagnosis of FASD were a history of maternal alcohol consumption obtained. Conclusions In a population of high-risk children seen in an adoption clinic, many had manifestations associated with FASD especially where prenatal alcohol exposure was established. The reported prevalence in this study is higher than that reported in our previous study of younger children. This is most likely due to the higher number of children diagnosed with alcohol-related neurodevelopmental disorders that typically manifest at an older age.